Laser Welding - Oliveira, João Pedro (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Laser welding is a high-energy process used in a wide range of advanced materials to obtain micro- to macro-sized joints in both similar and dissimilar combinations. Moreover, this technique is widely used in several industries, such as automotive, aerospace, and medical industries, as well as in electrical devices. Although laser welding has been used for several decades, significant and exciting innovations often arise from both the process and/or advanced materials side.